Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1038/ijo.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

Effects of licensed characters on children’s taste and snack preferences in Guatemala, a low/middle income country

Abstract: Licensed characters on food packaging influence Guatemalan children's taste and snack preferences. Given that these characters are typically used to promote high-energy, low-nutrient foods, their influence could contribute toward overconsumption of these foods and consequently increased risk of obesity in Guatemalan children. Therefore, public health advocates, in Guatemala and elsewhere, might explore restricting the use of licensed characters on food packaging as a public health strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 22 publications
3
73
0
9
Order By: Relevance
“…36 However, when we further investigated the impact of characters on food choice, we found that this varied based on age, sex, and specific character. Consistent with prior work on licensed media characters, 22 younger children (ages 6 to 7 years) were more attracted to products with characters than were older children (ages 8 to 9 years; H3a). Although on average children chose the more-healthful food less than 40% of the time, some characters (ie, Lightning McQueen and SpongeBob SquarePants) increased selection of healthy foods to approximately 64% among boys aged 6 to 7.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…36 However, when we further investigated the impact of characters on food choice, we found that this varied based on age, sex, and specific character. Consistent with prior work on licensed media characters, 22 younger children (ages 6 to 7 years) were more attracted to products with characters than were older children (ages 8 to 9 years; H3a). Although on average children chose the more-healthful food less than 40% of the time, some characters (ie, Lightning McQueen and SpongeBob SquarePants) increased selection of healthy foods to approximately 64% among boys aged 6 to 7.…”
Section: Discussionsupporting
confidence: 78%
“…20,21 However, the few studies that have examined such characters’ influence on older children (7 to 9 years old) suggest less influence among this age group. 22,23 In addition, data are lacking regarding the mechanisms through which these characters influence children, although Kraak and Story’s 19 synthesis of existing models provides a conceptual framework for inquiry on the topic. 19 One proposed mechanism is that cartoon characters capture children’s attention, 24 but only one study has examined the amount of attention cartoon characters in food marketing receive among older children.…”
mentioning
confidence: 99%
“…Nine studies involved children aged 2–6 years with a sample size ranging from n = 16–343 ; one study involved children aged 4–11 years ( n = 121) , and one study included children aged 8–11 years ( n = 208) (Table ). Only two studies reported details of ethnic and racial diversity, and the study conducted in Guatemala included only Latino children . Three studies measured sex differences , but noted no differences in the response of boys and girls to the characters used on the food products.…”
Section: Resultsmentioning
confidence: 99%
“…Child-oriented food marketing influences brand preferences and increases children's requests for food (Hastings G et al 2005; Letona et al 2014). Overweight and obese children have higher recognition of food advertisements and therefore food consumption, compared to their non-counterparts (Halford et al 2004).…”
Section: Introductionmentioning
confidence: 99%